2011
DOI: 10.1121/1.3533739
|View full text |Cite
|
Sign up to set email alerts
|

Trends in aircraft noise annoyance: The role of study and sample characteristics

Abstract: Recently, it has been suggested that the annoyance of residents at a given aircraft noise exposure level increases over the years. The objective of the present study was to verify the hypothesized trend and to identify its possible causes. To this end, the large database used to establish earlier exposure-response relationships on aircraft noise was updated with original data from several recent surveys, yielding a database with data from 34 separate airports. Multilevel grouped regression was used to determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 29 publications
1
33
0
Order By: Relevance
“…Several papers on possible changes in the annoyance response to noise have recently been published (van Kempen and van Kamp, 2005;Janssen et al, 2011). In a new report from the European Commission (Stansfeld et al, 2015), Janssen and Guski present a summary of aircraft noise studies conducted over the past 30-40 years.…”
Section: Discussionmentioning
confidence: 96%
“…Several papers on possible changes in the annoyance response to noise have recently been published (van Kempen and van Kamp, 2005;Janssen et al, 2011). In a new report from the European Commission (Stansfeld et al, 2015), Janssen and Guski present a summary of aircraft noise studies conducted over the past 30-40 years.…”
Section: Discussionmentioning
confidence: 96%
“…The association between noise exposure and noise annoyance has been extensively investigated, and aircraft noise has been found to be the most annoying noise source among all transportation noise sources when standardized for noise exposure level [6]. Recently, it has been suggested that annoyance due to aircraft noise has increased in previous years [5,16,17]. …”
Section: Introductionmentioning
confidence: 99%
“…Small changes in design, wording, item positioning, but also survey context or season may introduce variance of annoyance ratings which compromises the reliability and comparability of findings [1,2,3,4]. Owing to this, the research on survey context in the noise annoyance domain [5,6] and research about effects of the annoyance measurement scale employed [7,8] has recently gathered momentum.…”
Section: Introductionmentioning
confidence: 99%